PELATIHAN PERAWATAN MESIN JAHIT DALAM RANGKA RE-EKSISTENSI KELOMPOK SWADAYA MASYARAKAT (KSM) SEPAKAT DALAM PENGOLAHAN SAMPAH DI KELURAHAN PASAR UJUNG KABUPATEN KEPAHIANG - Suryono, Ahmad Fauzan; Arianti, Nyayu Neti; Reflis, Reflis (Martabe : Jurnal Pengabdian Kepada Masyarakat, 2021)
The Non-Governmental Organization (KSM) Sepakat is a form of community participation in waste processing. This KSM is located in Pasar Ujung Subdistrict, Kepahiang Regency, Bengkulu Province. KSM Sepakat was established in 2010 and from 2017 has stoped and vacuum from all activitiy to now. One of the factors that causes this vacuum is the damage to production equipment, including components in sewing machines. In addition, the lack of assistance and guidance from the local government has caused the motivation of the members to decrease so that production has decreased too. One of the efforts to re-exist and to reproduce again is sewing machine repair training to all KSM members. This training aims to ensure that each member has basic skills in repairing sewing machines so that if a damage occurs, it will not interfere with the production of waste processing. The method used in this training is through lectures, demonstrations, discussion and direct practice. From the results of the questionnaire, it can be seen that the participants can understand the material well and the material provided is in accordance with the problems in the field. Apart from that, from the questionnaire, it can be seen that the training participants are again committed to activating the activities at KSM Sepakat